Genetic parameters for test day milk traits and somatic cell counts in Chios dairy sheep - Ligda C.; Papadopoulos T.; Mavrogenis A.; Georgoudis A. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
The objective of the present study is to estimate of genetic and environmental factors affecting the incidence of mastitis in dairy sheep. The analysed data correspond to 2295 observations of the Chios flocks of the Agricultural Research Institution in Athalassa and the Agricultural Research Station of Chalkidiki. The traits analysed were milk yield, fat, protein percentage and somatic cell counts. The heritability estimates for milk yield, fat, protein and log2SCC were 0.35, 0.21, 0.31 and 0.14, respectively. Low negative genetic correlation was found between log2SCC and milk yield. The results indicated that somatic cell count could be used as a selection criterion for mastitis resistance in Chios sheep.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)